Relationship Between Financial Inclusion and Economic Growth: : Evidence From Ardl Modelling - Musa, Ibrahim; Magaji, Sule; Salisu, Ali (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
This study examines the impact of financial inclusion on economic growth in Nigeria. The statistical properties of data were tested using Zivot-Andrew unit root test. The Zivot Andrew unit root test indicates that gross domestic product, commercial bank branches (CBB) and mobile phone-based transactions are stationary at first difference while Automated Teller Machines (ATM) and foreign direct investment (FDI) are stationary at level. ATM has negative impact on GDP product in Nigeria. The long run coefficient shows that CBB has positive impact on GDP. ATM has positive impact on GDP. Mobile phone-based transaction has positive impact on GDP. FDI has positive impact on GDP. The error correction term (ECT) meets all the theoretical and statistical requirements both in the sign and size. This indicates that at 52.26% of the disequilibrium due to the shock in the previous years is adjusted back to the long run equilibrium in the current year. The Granger causality test shows that CBB, ATM, domestic depositors’ money in banks and FDI granger causes GDP while mobile phone-based transactions do not granger cause GDP. The study recommends that Central Bank of Nigeria should compel commercial banks to add the number of ATM in each branch.